Greener solvent-based processing of magnetoelectric nanocomposites - Lima, A. C. (2022)
Polymer-based magnetoelectric (ME) nanocomposites are an enabling material technology for a wide range of applications in the area of digitalization strategies. Due to its highest piezoelectric response among polymers, poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) is the piezoelectric matrix most used in polymer-based ME materials with over 80% of the total reports, with the resulting composites typically processed from solutions with N,N-dimethylformamide (DMF), a toxic solvent. Nevertheless, environmentally friendlier approaches and sustainable technologies are increasingly being required. This work demonstrates that P(VDF-TrFE)/Co2Fe2O4 nanocomposites can be successfully prepared from solution using three different environmentally friendlier solvents: dimethyl sulfoxide (DMSO), N,N′-dimethylpropyleneurea (DMPU), and triethyl phosphate (TEP) with different dipole moments. It is shown that the prepared composite films, with a maximum ME voltage coefficient of 35 mV cm–1 Oe–1 and a maximum sensitivity of 2.2 mV T–1, are suitable for applications, highlighting the path for a new generation of more sustainable ME sensors.